The Role of The Teacher in Increasing Students’ Interest in Study of Social Sciences at The State Middle High School 2 Tondano - Tuerah, Paulus Robert; Sumilat, Grystin Djein; Maukar, Nicky; Korompis, Manuel Vidi; Mesra, Romi; Rahman, Rahmania (Technium Social Sciences Journal, 2023)
The purpose of this study is to learn about the teacher’s attempts to increase student learning interest in social studies courses at The State Middle High School 2 Tondano. The approach employed is qualitative, with the major data gathering tools being observation, documentation, and interviews. Purposive sampling was used to choose the research sample, and the social studies instructor was chosen as the study informant. The data analysis method employed is qualitative analysis with three stages: data reduction, data presentation, and verification or conclusion. The findings of this study: (1) IPS topic instructors at The State Middle High School 2 Tondano have focused on preparations to boost students’ enthusiasm in learning Social Studies, such as creating lesson plans, developing acceptable learning objectives, creating learning resources, and defining relevant learning models. (2) The State Middle High School 2 Tondano teachers have made positive efforts to develop students’ interest in learning social studies by doing things like: creating a good learning atmosphere, providing motivation, developing student creativity, providing opportunities to submit creative ideas, providing guidance, providing a good learning environment, and rewarding students. Everything is done to pique students’ interest in social studies education.